The effect of educational IoT-related services on the performance of academicians in computer science colleges: A Review Paper: Review | Open Access | 30 April 2026 - Ruixuan, Shi; Syed Aris, Sharipah Ruzaina (EDUCATUM Journal of Science, Mathematics and Technology, 2026)
Technology plays a crucial role in enabling educators to access and utilize information, facilitating knowledge acquisition and effective learning. The presence of appropriate equipment is vital for creating a learning environment where educators can actively engage with ideas, process and apply them, and connect them to real-world contexts. The integration of IoT technologies in educational settings has the potential to revolutionize teaching and learning practices, but its specific impact on educators' performance requires further investigation. This review research focuses on examining the influence of IoT-related services in education on the performance of educators, with a particular emphasis on computer science colleges. The study encompasses primary research studies, academic papers, and reports that explore the effects of IoT-related services on educators' performance in computer science colleges. It identifies several factors that affect the effectiveness of educational IoT-related services, including the availability of technological infrastructure, the quality of training and professional development programs for educators, and the establishment of robust data security and privacy measures. By shedding light on the impact of educational IoT-related services on educators' performance in computer science colleges, this study contributes to the existing literature. The findings serve as a valuable resource for educational institutions seeking to understand the potential benefits and challenges associated with the successful implementation of IoT technologies in the academic field.